Safety and Efficacy of Selective, Clopidogrel-Based Strategies in Acute Coronary Syndrome: A Study-Level Meta-analysis - Patti, Giuseppe; Grisafi, Leonardo; Spinoni, Enrico Guido; Rognoni, Andrea; Mennuni, Marco (Thrombosis and Haemostasis, 2022)
Objectives To investigate outcomes with selective, clopidogrel-based therapies versus conventional treatment in patients undergoing percutaneous coronary intervention (PCI), especially for acute coronary syndrome.Background Safety and efficacy of alternative, selective, clopidogrel-based therapies after PCI are not robustly established.Methods We performed a study-level meta-analysis on six randomized trials investigating selective clopidogrel-based therapies (three on unguided de-escalation, N = 3,473; three on guided clopidogrel therapy, N = 7,533). Control groups received ticagrelor or prasugrel treatment. Main endpoints were major bleeding, any bleeding, major adverse cardiovascular events (MACE), and net clinical endpoint.Results The incidence of major bleeding and MACE was similar in the selective, clopidogrel-based therapy versus the conventional treatment arm (odds ratio [OR]: 0.72, 95% confidence interval [CI]: 0.51–1.01, p = 0.06; OR: 0.93, 0.72–1.20, p = 0.58; respectively). The rates of any bleeding were lower in the selective, clopidogrel-based therapy versus conventional treatment group (OR: 0.57, 95% CI: 0.40–0.80, p = 0.001); this greater safety was significant for unguided de-escalation (OR: 0.43, 95% CI: 0.32–0.58, p = 0.00001) and nonsignificant for guided clopidogrel therapy (OR: 0.72, 95% CI: 0.51–1.02, p = 0.07; p for interaction: 0.03). The incidence of the net clinical endpoint was fewer in the selective, clopidogrel-based therapy versus the conventional treatment arm (OR: 0.59, 95% CI: 0.41–0.85, p = 0.004); this benefit was significant for unguided de-escalation (OR: 0.50, 95% CI: 0.39–0.64, p < 0.00001) and nonsignificant for guided clopidogrel therapy (OR 0.85, 95% CI: 0.62–1.16, p = 0.30; p for interaction: 0.01).Conclusion As compared with prasugrel/ticagrelor treatment, alternative, selective, clopidogrel-based approaches provide a similar protection from cardiovascular events, reduce the risk of any bleeding, and are associated with a greater net benefit. These beneficial effects were prevalent with unguided de-escalation to clopidogrel.
Keywords: acute coronary syndrome; percutaneous coronary intervention; de-escalation; guided clopidogrel therapy; MACE